STRATEGI PERENCANAAN MERDEKA BELAJAR DI SMP NEGERI 3 SUNGGUMINASA - Satriani, Satriani; Baharuddin, Baharuddin; Damayanti, Eka; Syamsudduha, St. (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The independent learning program in secondary education is a program that must be implemented. However, not all schools can fully implement it because they are still looking for the right model. Therefore, there must be research that can be a best practice for other schools. This study aims to describe the planning of the independent learning program in the National Assessment activities, the simplified Learning Implementation Plan (RPP) activities, and the zoning system activities on the New Student Admission (PPDB) at SMP Negeri 3 Sungguminasa. This research is a type of descriptive qualitative research. Data were collected using interviews, observation, and documentation techniques. Data analysis used descriptive analysis techniques from Miles and Huberman through data reduction, data presentation, and conclusion. Test the validity of the data using extended observations, increasing persistence in research and triangulation techniques. The results of this study indicate that the planning of the independent learning program (in National Assessment activities, simplified RPP activities, and zoning system activities on PPDB at SMP Negeri 3 Sungguminasa has been running based on planning indicators, namely: (1) Determination of goals and objectives (2) Determine the resources used (3) Select and determine the method or method to be carried out. The findings imply that the school should be able to implement the independent learning policy not only in good planning but starting from implementation, and control, to the evaluation stage.